The Impact of Technology Integration in Learning on Increasing Student Engagement - Mufron, Ali; Maharjan, Kailie; Mark, Elladdadi; Xavier, Embrechts (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background:The Impact of Technology Integration in Learning on Increasing Student Engagement refers to how this technology integration can be used well in learning. With the integration of technology in learning, it will have a direct impact on students, both student involvement in using technology, as well as the impact on student activities and creativity. Research purposes:This research was conducted with the aim of finding out how much impact technology integration has on increasing student engagement. Apart from that, it also aims as an explanation of how important technology is today in the learning process. Method:The method used in this research is a quantitative method.This method is a way of collecting numerical data that can be tested. Data was collected through distributing questionnaires addressed to students. Furthermore, the data that has been collected from the results of distributing the questionnaire will be accessible in Excel format which can then be processed using SPSS. Results:From the research results, it can be stated that the impact of technology integration in learning can indeed have an influence on increasing student engagement. Because basically, today's students are more interested in using technology. However, as a teacher you also need to supervise your students in learning when using this technology. This aims to ensure that students actually use technology to learn. Conclusion:From this research, it can be concluded that the impact of technology integration in learning has a very big influence on student engagement. With technology, students can be creative in how they learn, increase students' knowledge in using technology, make students more enthusiastic about learning, and make students less likely to get bored while studying.